The Comparison of Transepithelial versus Conventional Photorefractive Keratectomy: Trans vs conventional PRK - Puspita Salfasari; Suhardjo; Indra Tri Mahayana (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction : Photorefractive keratectomy (PRK) is the first choice in treating myopia for eyes with mildly irregular and/or thin corneas because it preserves corneal integrity. A laser-assisted method for epithelial removal, termed Transepithelial PRK (T-PRK), was introduced as an alternative to conventional PRK, which gives a smoother corneal surface than that achieved with mechanical ablation of the epithelium in conventional PRK. Objective: To compare emmetropization between patients treated with T-PRK and conventional PRK. Methods: This study was an observative comparative analytic study with case-control study design. Myopic eyes treated by T-PRK (study group) were compared with variable-adjusted eyes treated by conventional PRK (control group), from year 2015-2018 at Dr.YAP Eye Hospital Yogyakarta. Patients were divided into 3 groups based on the degree on myopia; mild (spherical minus 0-3D), moderate (4-6D), and severe (>7D). Emmetropization within 1 month follow-up and treatment time were analyzed. Results: In all of the cases reviewed, the total percentage of patients treated with T-PRK who reached emmetropization within 1 month follow-up was 21.51% (17/79 eyes), with 33.34% (9/27 eyes) in mild, 28.57% (6/21 eyes) in moderate, and 6.45% (2/31 eyes) in severe myopia group; compared to the control group which was 22.78% (18/79 eyes) (p=0.848), with 48.14% (13/27 eyes) in mild, 15% (3/20 eyes) in moderate, and 6.25% (2/32 eyes) in severe myopia group. Treatment time in the study group was relatively faster compared to the control group. Conclusions: The study group showed slightly better result in treating moderate myopia within 1 month follow-up. Treatment time was relatively faster compared to the control group.